The assessment of material characteristic using vibration signal analysis during drilling process. - Inayatullah, Othman; Hamid, Faizal; Hew, Wei Hon; Jamaludin, Nordin; Abdullah, Shahrum (2014)
The purpose of this paper is to assess the material characteristic by using vibration signal analysis during drilling process. Generally, material with high mechanical properties exhibits low damping capacity and vice versa. The main objective of this paper is to develop a relationship between the signal parameters and the strengths of materials. Aluminium alloy 1100, stainless steel 304, and mild steel were selected as the specimens to be drilled using CNC machine. The vibration signal was captured using a transducer and recorded using a DAQ system. The signal parameters such as maximum amplitude, vibration energy, and the RMS value were extracted using MATLAB software. From the results obtained, the graphs of signal parameters versus strength of each specimen are plotted to show their relationship. It was found that the signal parameters increased exponentially as the strengths of materials increased. Besides that, the vibration signal of the specimens are analysed and compared based on their mechanical characteristics.